Humanitarian logistics meeting the challenge of preparing for and responding to disasters and complex emergencies - Heaslip, Graham; Tatham, Peter (London New York, NY Kogan Page Inc, 2023)
"In rapidly developing emergencies, it is vital for aid agencies to understand how to establish an agile supply chain that resists the chaos of a crisis and caters to unknown needs.In recent years, a number of global crises have highlighted the critical role that logistics plays in humanitarian response. From the distribution of the COVID-19 vaccine, to the providing of relief to victims of natural disasters, to the bringing of resources to a growing number of migrant crises, there is a vital need to understand how to conduct operations in confused and swiftly changing environments. This multi-contributed title contains chapters from a wide range of academics and practitioners who have worked in these situations, and offers cutting edge research into how these complex problems can be solved.Now in its 4th edition, Humanitarian Logistics is fully updated and contains new chapters on the challenge of obtaining scarce resources in the aftermath of a disaster, sustainability in a HL context, the logistics of the COVID-19 vaccine, the challenges of procurement in HL, a study of the humanitarian service performance system, cash-based HL systems and the interaction of blockchain and HL. Tightly organized by highly qualified editors, this book is essential reading for anyone who needs to understand how to effectively manage supply networks during a rapidly developing emergency"--
Includes bibliographical references and index.
Keywords: Business logistics; Emergency management; Humanitarian assistance